2022
DOI: 10.3389/fonc.2022.809304
|View full text |Cite
|
Sign up to set email alerts
|

Effective Combinations of Immunotherapy and Radiotherapy for Cancer Treatment

Abstract: Though single tumor immunotherapy and radiotherapy have significantly improved the survival rate of tumor patients, there are certain limitations in overcoming tumor metastasis, recurrence, and reducing side effects. Therefore, it is urgent to explore new tumor treatment methods. The new combination of radiotherapy and immunotherapy shows promise in improving therapeutic efficacy and reducing recurrence by enhancing the ability of the immune system to recognize and eradicate tumor cells, to overcome tumor immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 156 publications
0
26
0
Order By: Relevance
“…161 With further research, especially the discovery of radiation-induced stripping effects, scientists have found a potential link between radiotherapy and the immune microenvironment. 162,163 Recent clinical trials have shown that radiotherapy can induce immunogenic cell death (ICD), promote the release of tumor-associated antigens (TAAs), and then modify the TME to activate the immune system to provide an anti-tumor immune response. [163][164][165][166] Radiotherapy also alters the vascular endothelium of the tumor bed and promotes the release of chemokines, which causes the recruitment and entry of activated immune cells to the tumor site.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…161 With further research, especially the discovery of radiation-induced stripping effects, scientists have found a potential link between radiotherapy and the immune microenvironment. 162,163 Recent clinical trials have shown that radiotherapy can induce immunogenic cell death (ICD), promote the release of tumor-associated antigens (TAAs), and then modify the TME to activate the immune system to provide an anti-tumor immune response. [163][164][165][166] Radiotherapy also alters the vascular endothelium of the tumor bed and promotes the release of chemokines, which causes the recruitment and entry of activated immune cells to the tumor site.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…131 Immune checkpoint inhibitors (ICIs), tumor vaccines It is also used to protect patients from the harmful effects of radioimmunotherapy such as , adoptive cell therapy and cytokine therapy. 132 Radiotherapyrelated risks increase with increasing organ dose. 131 Several cell cycle checkpoint kinases and DNA damage-associated kinases have been engineered to compromise radiotherapy efficacy and target key signaling pathways.…”
Section: Radiation and Immunotherapymentioning
confidence: 99%
“…Radiotherapy is currently one of the most widely used cancer treatment methods in the clinic, but poor specificity of traditional in vivo radiotherapy, short-term effects in the tumor tissue and side effects on normal tissues, limit its wide application. Some multifunctional nanomaterials themselves can be used as radiotherapy sensitizing agents and radiation dose enhancers to effectively improve the efficacy of radiotherapy against the tumor lesions, thereby overcoming the dose tolerance constraints of healthy tissues and enhancing radiosensitization ( Yu et al, 2022 ). On the other hand, nanomaterials can be used as drug carriers to load different kinds of drugs to help regulate signaling pathways and cell cycles, inhibit DNA repair mechanisms, indirectly promote tumor cell apoptosis or selectively kill tumor cells and modulate the tumor microenvironment, which could improve the overall radiotherapy sensitivity ( Kwatra et al, 2013 ).…”
Section: Nano-drug Delivery Systems For Synergistic Antitumor Immunot...mentioning
confidence: 99%